STRATEGI GURU DALAM MENUMBUHKAN MINAT BELAJAR MEMBACA AL-QUR’AN PADA ANAK DI TAMAN PENDIDIKAN AL-QUR’AN BAITUL MUKARRAMAH BANJARMASIN - Ilsan Wahyu Saputra; Muhdi; Muhammad Rasyid Ridho (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The purpose of this study is to examine the methods teachers employ at Taman Pendidikan Al-Qur'an (TPA) Baitul Mukarramah Banjarmasin to encourage early childhood students' interest in learning to read the Qur'an, as well as the elements that facilitate and hinder learning. A qualitative descriptive method is used in this study. Observation, in-depth teacher interviews, and documentation were used to gather data. Thematic analysis, which included data reduction, data display, and conclusion drawing, was used to analyze the data. The study's findings demonstrate that educators use a variety of teaching techniques, including the Iqra' method, game-based learning, repetitive learning (muroja'ah), and individualized methods based on students' skill levels. These techniques have been shown to boost students' interest in and participation in Qur'anic reading assignments. Parental involvement, suitable learning facilities, and students' intrinsic motivation are examples of supporting factors. In the meantime, factors that hinder learning include students' weariness following formal education, a lack of parental supervision at home, and variations in their learning capacities. All things considered, teacher strategies are crucial for boosting kids' interest in studying the Qur'an, but for best outcomes, cooperation between educators, parents, and the classroom is required.